TELAAH WACANA DI AWAL KEPEMIMPINAN PRABOWO DALAM TAJUK RENCANA KEDAULATAN RAKYAT EDISI NOVEMBER - Afifah Qodri Rinjani; Astuty; Mulyani, Mimi (JURNAL SKRIPTA, 2025)
This research aims to explore how Kedaulatan Rakyat framed political issues at the beginning of Prabowo Subianto's leadership, including how the discourse construction influenced public perception. This research will also reveal the power relations hidden behind the text, as well as its impact on the socio-political dynamics in Indonesia. In addition, through this study, it is expected to identify the dominant discourse, ideological bias, and discursive strategies used by Kedaulatan Rakyat.The method used in this research is a descriptive qualitative research method using a critical discourse analysis perspective. The perspective used in this research is critical discourse analysis with the Norman Fairclough model. The data in this study are the issues raised by Kedaulatan Rakyat newspaper in the Opinion section of the Tajuk Rencana column on November 11, 13 and 15, 2024. The use of conjunctions and modality can create convincing and logical arguments. The study of conjunction complexity functions to connect ideas coherently and emphasize the logical relationship between clauses. In addition, an examination of the modality aspect can help convey the editor's attitude towards the issues raised, as well as strengthen the rhetoric, and provide a background for the argument. Through the examination of the use of conjunctions and modality, there are certain objectives. The objectives in production and consumption include (a) criticizing policies and behaviors with analytical schemes but still constructive, (b) increasing public moral awareness by emphasizing efforts through optimizing shared responsibility, (c) proposing realistic but hopeful solutions, such as revamping electricity subsidy data, developing human resources for downstream, or social media literacy.Keywords: Discourse Analyze; Editorial; Kedaulatan Rakyat